Answer: 4y/(y+3)
Explanation:
{(2y)(4y-12)}/{(y-3)(2y+6)}
= (8y^2 - 24y)/(2y^2 + 6y - 6y - 18)
= (8y^2 - 24y)/(2y^2 - 18)
= {8y(y-3)}/{2(y+3)(y-3)}
= 2 * 4y/{2(y+3)}
= 4y/(y+3)
Answer: the answer is x=-4.
Step-by-step explanation:
Multiply is product. Divide is quotient
Answer:
Each of them spent $9.35 on meal.
Step-by-step explanation:
Jacob and his three friends ordered an individual pizza and a drink for $6.19.
Total cost of pizza and drink = 6.19 × 4
= $24.76
They also ordered bread sticks for $4.25
Tax on the bill was = $2.39
Tip amount was = $1.50×4 = $6.0
So the total billed amount will be = 24.76 + 4.25 + 2.39 + 6
= $37.4
Since there were four persons including Jacob.
Therefore, each person spend on meal = ![\frac{37.40}{4}](https://tex.z-dn.net/?f=%5Cfrac%7B37.40%7D%7B4%7D)
= $9.35